Validity and reliability test for the questionnaire: The role of the existence of pharmacists on pharmaceutical services in public perceptions - Asrul Ismail (Jurnal Farmasi dan Ilmu Pengobatan, 2022)
Pharmacists have a massive role in the health care system. The pharmacist's paradigm shift, which initially focused on drugs and pharmaceutical supplies, changed to patient- and community-oriented. This change has an impact on the existence of pharmacists. Many attempts have been made to measure the extent of the pharmacist's role, one of which is by using a questionnaire. Research has been conducted on the validity and reliability of the questionnaire on public perceptions of the existence and role of pharmacists in pharmaceutical services. This study aimed to determine the validity and reliability of the pharmacist's role and existence questionnaire. This study uses the Cronbach Alpha method with the Pearson bivariate test. Questionnaires were distributed to 30 patients containing 28 questions consisting of 4 domains. There are two measurement scales: the Guttman scale and the Likert scale. The study results indicate that 28 questions have a greater significance than the r-table (0.361) on each scale. This means that the 28 questions are declared valid, while the reliability test shows an R-value of 0.588 for the Guttman scale and 0.905 for the Likert scale.